Polyphenols, Autophagy and Neurodegenerative Diseases: A Review - Vichitra Chandrasekaran; Tousif Ahmed Hediyal; Nikhilesh Anand; Pavan Heggadadevanakote Kendaganna; Vasavi Rakesh Gorantla; Arehally M. Mahalakshmi; Ruchika Kaul Ghanekar; Jian Yang; Meena Kishore Sakharkar; Saravana Babu Chidambaram (2023)
Polyphenols are secondary metabolites from plant origin and are shown to possess a wide range of therapeutic benefits. They are also reported as regulators of autophagy, inflammation and neurodegeneration. The autophagy pathway is vital in degrading outdated organelles, proteins and other cellular wastes. The dysregulation of autophagy causes proteinopathies, mitochondrial dysfunction and neuroinflammation thereby contributing to neurodegeneration. Evidence reveals that polyphenols improve autophagy by clearing misfolded proteins in the neurons, suppress neuroinflammation and oxidative stress and also protect from neurodegeneration. This review is an attempt to summarize the mechanism of action of polyphenols in modulating autophagy and their involvement in pathways such as mTOR, AMPK, SIRT-1 and ERK. It is evident that polyphenols cause an increase in the levels of autophagic proteins such as beclin-1, microtubule-associated protein light chain (LC3 I and II), sirtuin 1 (SIRT1), etc. Although it is apparent that polyphenols regulate autophagy, the exact interaction of polyphenols with autophagy markers is not known. These data require further research and will be beneficial in supporting polyphenol supplementation as a potential alternative treatment for regulating autophagy in neurodegenerative diseases.